Assessing Food Safety Risks in Wafer Production: Menilai Risiko Keamanan Pangan dalam Produksi Wafer - Yuwana, Nurria Peppi; Wahyuni, Hana Catur (Universitas Muhammadiyah Sidoarjo, 2024)
Ensuring food safety and halal compliance is crucial for the competitiveness of food products, especially in Indonesia where issues with unsafe and non-halal food distribution persist. This research investigates the implementation of food safety and halal systems in the wafer production process. Through employee interviews and utilizing the 5W + 1H method, alternative strategies and risk controls are identified. The study reveals that the company's efforts to enhance food safety and halal compliance include implementing the HACCP system and the Halal Product Guarantee System. Observations indicate that continuous monitoring of the HACCP system in the production area is essential for improving food quality and safety. This research bridges a gap in understanding the implementation of food safety and halal systems in the food industry, providing insights for companies aiming to enhance their practices and meet regulatory requirements effectively. Highlights : Investigation into food safety and halal systems in wafer production. Utilization of employee interviews and 5W + 1H method for analysis. Implementation of HACCP and Halal Product Guarantee System to enhance compliance and quality. Keywords : Food safety, halal compliance, wafer production, HACCP system, risk controls